Effects of foliar application herbicides to control semi-parasitic plant Arceuthobium oxycedri - MOHAMMAD REZA KAVOSI; FERIDON FARIDI; GOODARZ HAJIZADEH (Smujo International, 2012)
Abstract. Kavosi MR, Faridi F, Hajizadeh G. 2012. Effects of foliar application herbicides to control semi-parasitic plant Arceuthobium oxycedri. Nusantara Bioscience 4: 76-80. Epiphytes are plants growing on the stem and branches of other growing plants. Dwarf mistletoe (Arceuthobium oxycedri) is one of the important macro epiphytes or semi-parasitic plant, is able to damage Junipers and provide favorable conditions for bother damaging factors such as pest, disease, rodent animals and vulnerability to unfavorable climate conditions. In this study used herbicides in three concentrations (1.35, 1.93, 2.7 g of Roundup, 0.675, 0.964, 1.35 g of Basagran, and 0.9, 1.28, 1.8 g of Gramoxone in1000 mL water) and three replications to examine the impact of each herbicide on A. oxycedri at Junipers forests in areas located at the East Gorgan state region, North of Iran. The results from Basagran on 95.55% dwarf mistletoe indicated that the plant was dried completely up. Roundup dried 61.67% of dwarf mistletoe. Gramoxone causes the lowest percent of dryness (23.89%). By analyzing results about the impact of herbicides on percentage of measuring dryness, there is difference in level significant 1% between herbicides. The impact of each herbicide on A. oxycedri showed that concentration-3 has more impact on increasing dwarf mistletoe dryness but with concentration-2 it has less difference. Ultimately concentration-2 Basagran can be used to reduce costs in order to control dwarf mistletoe.